NEW EXACT SOLUTIONS OF THE SPACE-TIME FRACTIONAL KdV-BURGERS AND NON-LINEAR FRACTIONAL FOAM DRAINAGE EQUATION - Cevikel, Adem Cengiz (VINCA INST NUCLEAR SCI, 2018)
The fractional differential equations have been studied by many authors and some effective methods for fractional calculus were appeared in literature, such as the fractional sub-equation method and the first integral method. The fractional complex transform approach is to convert the fractional differential equations into ordinary differential equations, making the solution procedure simple. Recently, the fractional complex transform has been suggested to convert fractional order differential equations with modified Riemann-Liouville derivatives into integer order differential equations, and the reduced equations can be solved by symbolic computation. The present paper investigates for the applicability and efficiency of the exp-function method on some fractional non-linear differential equations.
Keywords: fractional differential equation; exact solutions; exp-function method; PERIODIC-SOLUTIONS; COMPLEX TRANSFORM; SOLITON-SOLUTIONS; PHYSICAL MODELS; Thermodynamics